Development of a Sox2 reporter system modeling cellular heterogeneity in glioma. Issue 3 (21st November 2014) - Stoltz, Kevin; Sinyuk, Maksim; Hale, James S.; Wu, Qiulian; Otvos, Balint; Walker, Kiera; Vasanji, Amit; Rich, Jeremy N.; Hjelmeland, Anita B.; Lathia, Justin D.
Abstract: Background: Malignant gliomas are complex systems containing a number of factors that drive tumor initiation and progression, including genetic aberrations that lead to extensive cellular heterogeneity within the neoplastic compartment. Mouse models recapitulate these genetic aberrations, but readily observable heterogeneity remains challenging. Methods: To interrogate cellular heterogeneity in mouse glioma models, we utilized a replication-competent avian sarcoma-leukosis virus long terminal repeat with splice acceptor/tumor virus A (RCAS-tva) system to generate spontaneous mouse gliomas that contained a Sox2-enhanced green fluorescent protein (EGFP) reporter. Glial fibrillary acidic protein-tva mice were crossed with Sox2–EGFP mice, and tumors were initiated that contained a subpopulation of Sox2–EGFP-high cells enriched for tumor-initiating cell properties such as self-renewal, multilineage differentiation potential, and perivascular localization. Results: Following implantation into recipient mice, Sox2–EGFP-high cells generated tumors containing Sox2–EGFP-high and Sox2–EGFP-low cells. Kinomic analysis of Sox2–EGFP-high cells revealed activation of known glioma signaling pathways that are strongly correlated with patient survival including platelet-derived growth factor receptor beta, phosphoinositide-3 kinase, and vascular endothelial growth factor. Our functional analysis identified active feline sarcoma (Fes) signaling in Sox2–EGFP-high cells. Fes negatively correlated with glioma patient survival and was coexpressed with Sox2-positive cells in glioma xenografts and primary patient-derived tissue. Conclusions: Our RCAS-tva/Sox2-EGFP model will empower closer examination of cellular heterogeneity and will be useful for identifying novel glioma pathways as well as testing preclinical treatment efficacy.